(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background : To assess the diagnostic accuracy of aspiration cytology as a pre-operative screening procedure and this study was done to reach a consensus and to find out the best diagnostic tool for assessment of thyroid swellings pre-operatively. Materials and methods : A cross sectional study was carried out in the Department of Otolaryngology & Head Neck Surgery of Chittagong Medical College Hospital (CMCH) between March 2014 to March 2015. Total 50 patients were included in the study, where pre-operative Fine Needle Aspiration Cytology (FNAC) and post operative histopathology were done to find out the correlation. Data were analyzed and presented as both qualitative and quantitative data as applicable using SPSS version 20. The quantitative data were analyzed by mean, standard deviation. The qualitative data were analyzed by Mc NEMAR test (Mc NEMAR c2 test). Results : 50 cases were included in the study. FNAC revealed 40 non- neoplastic lesion, 5 papillary carcinoma, 4 follicular neoplasm and 1 was suspicious for malignancy. Histopathology revealed 38 non neoplastic and 2 neoplatic lesion among 40 non neoplastic cases. 5 cases which were diagnosed as papillary carcinoma thyroid on FNAC were also proved to be same on histopathology. Out of 4 follicular neoplasm 1 was non neoplastic and other 3 were neoplstic. The suspicious for malignancy lesion was proved as cystic papillary carcinoma on histopathology. The sensitivity of FNAC was 81.82%, specificity was 97.44%, positive predictive value was 90%, negative predictive value was 95% and accuracy was 94%. Conclusion : FNAC of Thyroid is more specific then sensitive with high accuracy rate. Therefore FNAC should be adopted as an initial investigation of thyroid disease. JCMCTA 2019 ; 30 (2) : 36-40